(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Arun Jhoshi’s fourth and Sahitya Academy Winner novel The Last Labyrinth (1981) is of god sizeand is dedicated to the three children of Joshi. Here, the central figure isSom Bhaskar, a multimillionaire married to a woman of his choice, Geeta, whohas borne him two children. But Bhaskar is an ever dissatisfied, restlessperson, who is relentlessly driven by undefined hungers of possession – of anobject, a business-enterprise and a woman. Searching for a meaning of life anddeath, Som confronts with the dilemmas and contradictions.